2016
DOI: 10.3748/wjg.v22.i25.5718
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative, intraoperative and postoperative risk factors for anastomotic leakage after laparoscopic low anterior resection with double stapling technique anastomosis

Abstract: Anastomotic leakage (AL) is one of the most devastating complications after rectal cancer surgery. The double stapling technique has greatly facilitated intestinal reconstruction especially for anastomosis after low anterior resection (LAR). Risk factor analyses for AL after open LAR have been widely reported. However, a few studies have analyzed the risk factors for AL after laparoscopic LAR. Laparoscopic rectal surgery provides an excellent operative field in a narrow pelvic space, and enables total mesorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 109 publications
1
69
0
2
Order By: Relevance
“…There is a lack of understanding as to whether or not delayed AL is different from early AL. Reported risk factors for early AL following rectal surgery are low level of anastomosis, male gender, and the presence of intraoperative adverse events [ 6 8 ], which may correlate to the degree of surgical difficulty. In terms of the timeframe in which delayed AL develops, delayed AL does not seem to be attributable to technical factors, but rather to other predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lack of understanding as to whether or not delayed AL is different from early AL. Reported risk factors for early AL following rectal surgery are low level of anastomosis, male gender, and the presence of intraoperative adverse events [ 6 8 ], which may correlate to the degree of surgical difficulty. In terms of the timeframe in which delayed AL develops, delayed AL does not seem to be attributable to technical factors, but rather to other predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Anastomotic leakage (AL) is one of the most dreadful postoperative complications of colorectal cancer because it can result in increased morbidity and mortality as well as poorer long-term prognosis. Reported incidence rates of colorectal AL vary between 3 and 20% [ 6 8 ]. Although most studies of AL have limited their investigation time to a period of postoperative 30 days, some studies have shown that AL can occur more than 30 days postoperatively [ 9 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reported postoperative occurrence risk is 2.2%-12% [47], despite the advancements in laparoscopic techniques and the well-accepted concept of total mesocolic excision. The blood supply and tension of the anastomosis are two major factors affecting the rate of anastomotic leakage [48]. In our opinion, for cancers located in the descending colon or the sigmoid colon, the ligation of the sigmoid artery and superior rectal artery would greatly compromise blood supply of the bowel distal to the anastomosis stoma.…”
Section: Discussionmentioning
confidence: 91%
“…They analyzed the tumor size and the recompression before stapler firing was risk factors for AL after laparoscopic LAR with DST anastomosis. He also reviewed preoperative, intraoperative and postoperative risk factors for anastomotic leakage after laparoscopic low anterior resection with DST anastomosis [11]. Multiple staple firing and diameter of circular stapler are intraoperative risk factors.…”
Section: Discussionmentioning
confidence: 99%